The influence of the accuracy of providing capital, entrepreneurship training and promotion strategies on the success of the 2013 Student Entrepreneurship Program (PMW) at the State University of Semarang - Lili Sulasi (Indonesia Accounting Research Journal, 2021)
The business success of the 2013 student entrepreneur program participants was relatively low when viewed from the percentage rate of return on capital assistance of 10.40% and business continuity of 42.55%. This situation shows that in running their business they face obstacles that result in low business success. The purpose of this study was to determine the effect of the appropriate provision of capital assistance, entrepreneurship training and promotion strategies on business success. The results showed that the effect of the accuracy of providing capital assistance, entrepreneurship training and promotion strategies simultaneously was 71% and the partial effect of each variable on the accuracy of providing capital assistance was 10.56%, entrepreneurship training was 19.36% and promotion strategy was 25. 40% to business success. Suggestions that can be given by the author in this study for the implementation of the student entrepreneur program (PMW) include capital requirements for businesses that must be met by providing an amount of funds that are in accordance with the business needs listed in the business plan and for the implementation of mentoring it is necessary to increase the intensity again by providing rules to participants to conduct consultations with a minimum limit that must be met. Participants are expected to be able to increase advertising by using media that attracts purchase interest such as: brochures, posters, banners and so on.